Efficient moisture-absorbing, breathable and self-cleaning automotive interior non-woven fabric and preparation method thereof
By modifying the superposition structure of the collagen fiber mesh and the surface treatment of the nanoparticle, an efficient moisture-absorbing and breathable and self-cleaning automobile interior non-woven fabric is prepared, which solves the problem of performance degradation when the temperature rises and achieves good moisture-absorbing and breathable and self-cleaning in high-temperature environments.
Patent Information
- Application Number
- CN202411562304.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-05
Smart Images

Figure CN119571541A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of layer structure materials, in particular to a method for preparing a layer structure non-woven fabric material made of animal raw materials, and in particular to a highly efficient moisture-absorbing, breathable and self-cleaning automobile interior non-woven fabric and a method for preparing the same. Background Art
[0002] With the continuous progress of the automobile industry, automobile production and sales continue to grow, and the demand for interior materials has also increased. While pursuing automobile performance, automobile manufacturers are also paying more and more attention to the comfort, environmental protection and economy of interior materials. As a lightweight, environmentally friendly, beautiful and cost-effective material, non-woven fabrics have gradually become an important choice for automobile interiors.
[0003] The sound absorption and water absorption of collagen fibers make them a potential high-quality material for automotive interiors. The interior of a car requires certain sound-absorbing materials to reduce noise and improve driving and riding comfort, and the sound absorption performance of collagen fibers can meet this demand. At the same time, its water absorption also helps to regulate the humidity inside the car and create a more comfortable environment. Collagen fibers are widely distributed in nature, making them easy to obtain. Collagen fibers are widely distributed in various organs and are most abundant in tissues such as skin, sclera, tendons, ligaments, joint capsules, and blood vessels. They can be made into biomass conversion materials.
[0004] Under direct sunlight, the temperature inside the car may rise to 50°C to 80°C or even higher in a short period of time. The relative humidity in the air decreases under high temperatures, which may cause the moisture absorption capacity of the interior materials to decrease and fail to effectively absorb moisture or sweat in the car. Excessive temperature will cause the collagen fibers to shrink immediately, and as the temperature continues to rise, the degree of shrinkage gradually increases, causing the fiber structure to be destroyed and causing the collagen fibers to lose their water absorption. High temperature may affect the reactivity of photocatalytic materials. Although temperature promotes certain chemical reactions, excessively high temperatures may cause the catalyst to fail or the reaction to become unstable, thereby weakening the self-cleaning effect. Under high temperature conditions, dirt and impurities in the car may be more likely to adhere to the surface. If the superhydrophobic effect is insufficient or the coating ages, dirt will accumulate and affect the appearance and hygiene of the interior.
[0005] Therefore, it is necessary to improve the automotive interior nonwoven fabric in the prior art to solve the above problems. Summary of the invention
[0006] The present invention overcomes the deficiencies of the prior art and provides a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automobile interior decoration and a preparation method thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior non-woven fabric, comprising the following steps:
[0008] S1: preparing a collagen-polyester composite fiber into a collagen fiber net, performing a hydrophobic surface treatment on one side of the collagen fiber net and then spraying nano-silicon dioxide particles and nano-titanium dioxide particles thereon, and performing a hydrophilic surface treatment on the other side and then spraying nano-zinc oxide particles thereon, to obtain a modified collagen fiber net, wherein the collagen-polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber;
[0009] S2: preparing a lyocell fiber web from lyocell fibers, soaking the lyocell fiber web in an alkaline solution for 1-2 hours, taking out and drying the lyocell fiber web to obtain a modified lyocell fiber web;
[0010] S3: stacking the modified collagen fiber web in S1 and the modified lyocell fiber web in S2, wherein one modified collagen fiber web is stacked on each side of the modified lyocell fiber web, and the side of the modified collagen fiber web containing the nano zinc oxide particles is in close contact with the modified lyocell fiber web, to obtain a multilayer fiber web;
[0011] S4: The multilayer fiber web in S3 is subjected to the steps of stretching, hydroentanglement and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automobile interior decoration.
[0012] In a preferred embodiment of the present invention, the preparation method of the collagen polyester composite fiber in S1 is: dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wet spinning the collagen polyester composite solution to obtain collagen polyester composite fibers, and the solvent of the collagen polyester composite solution is a mixed solution obtained by mixing acetic acid with a concentration of 2%-5% and DMF in a ratio of 1:1-2:1.
[0013] In a preferred embodiment of the present invention, the mass ratio of the collagen fiber to the polyester fiber is 3:7-5:5, the collagen fiber is type I collagen fiber, the collagen fiber is hydrolyzed with pepsin before being dissolved, and the mass ratio of the pepsin to the collagen fiber is 1:50-200.
[0014] In a preferred embodiment of the present invention, after the collagen polyester composite solution is wet-spun, the spun yarn is freeze-dried, the freeze-drying temperature is -85 to -60°C, and the freeze-drying time is 36-48 hours.
[0015] In a preferred embodiment of the present invention, the particle diameter of the nano silicon dioxide particles in S1 is 400-500 nm, the particle diameter of the nano titanium dioxide particles is 100-200 nm, and the particle diameter of the nano zinc oxide particles is 200-300 nm.
[0016] In a preferred embodiment of the present invention, the fineness of the collagen polyester composite fiber in S1 is 10-15D, and the mass ratio of the nano-silicon dioxide particles, the nano-titanium dioxide particles, the nano-zinc oxide particles and the collagen fiber network is: 1:1-1.5:0.8-1.2:100-150.
[0017] In a preferred embodiment of the present invention, the alkaline solution in S2 is a sodium hydroxide solution, and the concentration of the alkaline solution is 10-15%.
[0018] In a preferred embodiment of the present invention, the mass ratio of the total mass of the modified collagen fiber web in S3 to the mass of the modified lyocell fiber web is 1:2-2.6.
[0019] In a preferred embodiment of the present invention, the spunlace process in S4 is selected from flat mesh spunlace and drum spunlace, and the water pressure of the spunlace process is 60-250 bar.
[0020] In order to achieve the above-mentioned purpose, the second technical solution adopted by the present invention is: a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automobile interior decoration.
[0021] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0022] (1) The present invention provides a method for preparing an efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automobile interior decoration. The modified collagen fiber web has a super-hydrophobic structure and a super-hydrophilic structure. The surface of the super-hydrophilic structure is in close contact with the modified lyocell fiber web, so that the non-woven fabric has both moisture-absorbing and breathable capabilities and self-cleaning capabilities. Low shrinkage and porous materials are used. Compared with the non-woven fabric preparation method in the prior art, the pore size of the non-woven fabric can be maintained when the temperature rises, and the moisture-absorbing, breathable and self-cleaning properties of the non-woven fabric are maintained. The non-woven fabric has the ability to resist temperature changes, so that the non-woven fabric has good moisture-absorbing, breathable and self-cleaning properties when the temperature rises, thereby solving the defect of reduced moisture-absorbing, breathable and self-cleaning properties of the automobile interior decoration non-woven fabric in the prior art.
[0023] (2) In the present invention, freeze drying is used to treat the fibers, and the water is directly sublimated from the solid state to the gas state at low temperature, thereby eliminating the water in the fibers and forming an aerogel structure. Compared with the prior art, the thermal stress caused by water evaporation is reduced, and the performance of the porous structure can be improved, and thermal shrinkage can be avoided when heated, thereby maintaining the pore structure and moisture permeability of the non-woven fabric when the temperature rises.
[0024] (3) In the present invention, the particle diameter of the nano-silicon dioxide particles is 400-500nm, the particle diameter of the nano-titanium dioxide particles is 100-200nm, and the particle diameter of the nano-zinc oxide particles is 200-300nm. Nanoparticles of various specifications and diameters form a multi-scale rough structure on the fiber surface. Compared with the prior art, this structure can enhance the super-hydrophobic properties of the material, is conducive to the formation of an air cushion layer, and reduces the contact area between the liquid and the material surface, thereby ensuring self-cleaning performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 It is a method step diagram of a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0029] like Figure 1 As shown, a method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automobile interior decoration comprises the following steps:
[0030] S1: The collagen polyester composite fiber is made into a collagen fiber net, and one side of the collagen fiber net is subjected to a hydrophobic surface treatment and then sprayed with nano-silicon dioxide particles and nano-titanium dioxide particles, and the other side is subjected to a hydrophilic surface treatment and then sprayed with nano-zinc oxide particles to obtain a modified collagen fiber net. The collagen polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber; the nano-silicon dioxide and nano-titanium dioxide particles provide hydrophobicity, while the nano-zinc oxide particles provide hydrophilicity. These nanoparticles can still maintain their surface properties at high temperatures, which helps to maintain the moisture absorption, breathability and self-cleaning properties of the non-woven fabric. Collagen fibers are derived from biomass materials.
[0031] S2: making lyocell fiber into a lyocell fiber web, soaking the lyocell fiber web in an alkaline solution for 1-2 hours, taking out and drying, and obtaining a modified lyocell fiber web; the lyocell fiber web is modified by soaking in an alkaline solution, which can increase the hydrophilicity of the fiber and improve its moisture absorption capacity at high temperature.
[0032] S3: The modified collagen fiber net in S1 and the modified lyocell fiber net in S2 are stacked in such a way that a modified collagen fiber net is stacked on each side of the modified lyocell fiber net, and the side of the modified collagen fiber net containing the nano zinc oxide particles is in close contact with the modified lyocell fiber net to obtain a multi-layer fiber net; the stacking of the modified collagen fiber net and the modified lyocell fiber net makes the non-woven fabric have a multi-layer structure, which helps to improve its stability and performance at high temperatures. This arrangement can promote the absorption of moisture remaining on the surface of the non-woven fabric into the modified lyocell fiber net under the huge difference in humidity coefficient between super-hydrophobicity and super-hydrophilicity.
[0033] S4: The multi-layer fiber web in S3 is subjected to the steps of stretching, spunlacing and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior nonwoven fabric. The stretching process can improve the orientation and arrangement of the fibers, the spunlacing process can fix the position of the fibers to form a stable nonwoven fabric structure, and the drying process helps to fix the final form of the nonwoven fabric and helps to maintain the structure and performance of the nonwoven fabric at high temperatures.
[0034] The modified collagen fiber mesh has a super-hydrophobic structure and a super-hydrophilic structure. The surface of the super-hydrophilic structure is in close contact with the modified lyocell fiber mesh, so that the non-woven fabric has both moisture absorption and breathability and self-cleaning ability. Low shrinkage and porous materials are used, so that the pore size of the non-woven fabric can be maintained when the temperature rises, and the moisture absorption, breathability and self-cleaning properties of the non-woven fabric are maintained. The non-woven fabric has the ability to resist temperature changes, so that the non-woven fabric can have good moisture absorption, breathability and self-cleaning properties when the temperature rises, thereby solving the defect of reduced moisture absorption, breathability and self-cleaning properties of automotive interior non-woven fabrics in the prior art when the temperature rises.
[0035] The preparation method of the collagen polyester composite fiber in S1 is: dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wet spinning the collagen polyester composite solution to obtain collagen polyester composite fibers, and the solvent of the collagen polyester composite solution is a mixed solution obtained by mixing acetic acid with a concentration of 2%-5% and DMF in a ratio of 1:1-2:1.
[0036] Using 2%-5% acetic acid and DMF mixed in a ratio of 1:1-2:1 as a solvent helps to dissolve the collagen fiber and polyester fiber to form a uniform collagen polyester composite solution. This mixed solvent helps to spin the fibers uniformly, thereby forming a uniform fiber network in the non-woven fabric, which helps to maintain its moisture absorption and breathability.
[0037] The blend of collagen fibers and polyester fibers can provide good mechanical properties and thermal stability. Collagen fibers provide biocompatibility and hydrophilicity, while polyester fibers provide strength and heat resistance. This composite material can maintain its structure and function at high temperatures, helping the nonwoven fabric maintain moisture permeability and self-cleaning properties when heated.
[0038] Wet spinning is a method of forming fibers in a coagulation bath. This method allows the fibers to form a specific structure during the coagulation process, which helps to improve the strength and stability of the fibers. The fibers after wet spinning have a certain moisture content. The freeze-drying treatment after spinning helps to fix the structure of the fibers and eliminate the moisture in the fibers, forming an aerogel structure. The aerogel structure has a continuous nanoscale porous network, and the heat exchange efficiency is extremely low when air flows through it, so it has excellent thermal insulation properties. The high porosity structure of aerogel helps air circulation, improves the air permeability of non-woven fabrics, and maintains good air exchange even in high temperature environments.
[0039] When freeze-drying is used to treat the fibers, water sublimates directly from solid to gas at low temperatures, avoiding the formation of liquid water, reducing the thermal stress caused by water evaporation, and avoiding thermal shrinkage when heated, thereby maintaining the pore structure and moisture permeability of the non-woven fabric when the temperature rises.
[0040] The mass ratio of collagen fiber to polyester fiber is 3:7-5:5. Type I collagen fiber is selected as the collagen fiber. Pepsin is used to hydrolyze the collagen fiber before dissolving. The mass ratio of pepsin to collagen fiber is 1:50-200.
[0041] Using pepsin to hydrolyze collagen fibers can effectively break down large molecular collagen into smaller peptide chains or amino acids to expose more carboxyl groups, amino groups, peptide bonds, etc., which can promote the binding ability between collagen and nanoparticles.
[0042] Type I collagen fiber is the most common type of collagen in the human body, with good biocompatibility and mechanical properties. The use of type I collagen fiber can improve the strength and durability of non-woven fabrics. Polyester fiber has a high melting point and glass transition temperature. When mixed with collagen fiber, it can improve the overall thermal stability of non-woven fabrics, making it less likely to deform when heated.
[0043] After the collagen polyester composite solution is wet-spun, the spun yarn is freeze-dried at a temperature of -85 to -60°C for 36 to 48 hours. The low temperature during the freeze-drying process helps maintain the original structure and morphology of the fiber, avoids fiber shrinkage or deformation caused by high temperature, and thus maintains the integrity and performance of the non-woven fabric.
[0044] The particle diameter of the nano-silicon dioxide particles in S1 is 400-500nm, the particle diameter of the nano-titanium dioxide particles is 100-200nm, and the particle diameter of the nano-zinc oxide particles is 200-300nm. Nanoparticles of different diameters form a multi-scale rough structure on the fiber surface, which can enhance the super-hydrophobic properties of the material, facilitate the formation of an air cushion, reduce the contact area between the liquid and the material surface, and thus improve the self-cleaning performance.
[0045] The fineness of the collagen polyester composite fiber in S1 is 10-15D, and the mass ratio of nano-silicon dioxide particles, nano-titanium dioxide particles, nano-zinc oxide particles and collagen fiber net is 1:1-1.5:0.8-1.2:100-150. By precisely controlling the mass ratio of fibers and particles, the non-woven fabric can still maintain good moisture absorption, air permeability and self-cleaning properties when the temperature rises, solving the problem of performance degradation of automotive interior non-woven fabrics in the prior art when the temperature rises.
[0046] The alkaline solution in S2 is a sodium hydroxide solution, and the concentration of the alkaline solution is 10-15%. The fiber web treated with alkali can form more microporous structures during the spunlace and drying process, and these micropores help to improve the air permeability of the non-woven fabric.
[0047] The mass ratio of the total mass of the modified collagen fiber web to the mass ratio of the modified lyocell fiber web in S3 is 1:2-2.6. The appropriate mass ratio helps to form a more stable nonwoven structure during the drawing and spunlace process, thereby improving the overall performance of the nonwoven fabric. By adjusting the mass ratio, a balance of the properties of the collagen fiber web and the lyocell fiber web can be achieved. Collagen fibers provide biocompatibility and hydrophilicity, while lyocell fibers provide mechanical strength and softness. This ratio helps the nonwoven fabric maintain its overall performance when heated.
[0048] The spunlace process in S4 uses either flat mesh spunlace or rotary drum spunlace, and the water pressure of the spunlace process is 60-250 bar. The spunlace process uses high-pressure water flow to displace, interweave and entangle the fibers in the fiber web, forming flexible entanglement points, thereby strengthening the fiber web. This entanglement helps to improve the mechanical properties of the nonwoven fabric and keep its structure stable when heated.
[0049] In order to achieve the above-mentioned purpose, the second technical solution adopted by the present invention is: a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automobile interior decoration.
[0050] Embodiment 1
[0051] This embodiment prepares a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior nonwoven fabric, and the preparation process is as follows:
[0052] S1: Dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wherein the solvent of the collagen polyester composite solution is a mixture of 4% acetic acid and DMF in a ratio of 2:1, the mass ratio of the collagen fibers to the polyester fibers is 2:8, type I collagen fibers are selected as collagen fibers, and the collagen fibers are hydrolyzed with pepsin before being dissolved, and the mass ratio of pepsin to the collagen fibers is 1:50-200; wet spinning the collagen polyester composite solution, and freeze drying the solution, the freeze drying temperature is -70°C, and the freeze drying time is 40h, to obtain collagen polyester composite fibers.
[0053] The collagen polyester composite fiber is made into a collagen fiber net, and one side of the collagen fiber net is subjected to a hydrophobic surface treatment and then sprayed with nano-silicon dioxide particles and nano-titanium dioxide particles, and the other side is subjected to a hydrophilic surface treatment and then sprayed with nano-zinc oxide particles to obtain a modified collagen fiber net. The collagen polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber; the particle diameter of the nano-silicon dioxide particles is 400nm, the particle diameter of the nano-titanium dioxide particles is 100nm, and the particle diameter of the nano-zinc oxide particles is 250nm; the fineness of the collagen polyester composite fiber is 15D, and the mass ratio of the nano-silicon dioxide particles, the nano-titanium dioxide particles, the nano-zinc oxide particles and the collagen fiber net is 1:1.5:1.2:150.
[0054] S2: preparing a lyocell fiber web from lyocell fiber, soaking the lyocell fiber web in an alkaline solution for 1 hour, taking out and drying the lyocell fiber web to obtain a modified lyocell fiber web; the alkaline solution is a 10% concentration sodium hydroxide solution.
[0055] S3: The modified collagen fiber net in S1 and the modified lyocell fiber net in S2 are stacked in such a way that a modified collagen fiber net is stacked on each side of the modified lyocell fiber net, and a side of the modified collagen fiber net containing nano zinc oxide particles is closely attached to the modified lyocell fiber net to obtain a multi-layer fiber net; the ratio of the total mass of the modified collagen fiber net to the mass of the modified lyocell fiber net is 1:2.
[0056] S4: The multi-layer fiber web in S3 is subjected to the steps of stretching, hydroentanglement and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automotive interior decoration.
[0057] Embodiment 2
[0058] This embodiment prepares a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior nonwoven fabric, and the preparation process is as follows:
[0059] S1: Dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wherein the solvent of the collagen polyester composite solution is a mixture of 4% acetic acid and DMF in a ratio of 2:1, the mass ratio of the collagen fibers to the polyester fibers is 3:7, type I collagen fibers are selected as collagen fibers, and the collagen fibers are hydrolyzed with pepsin before being dissolved, and the mass ratio of pepsin to the collagen fibers is 1:50-200; wet spinning the collagen polyester composite solution, and freeze drying the solution, the freeze drying temperature is -70°C, and the freeze drying time is 40h, to obtain collagen polyester composite fibers.
[0060] The collagen polyester composite fiber is made into a collagen fiber net, and one side of the collagen fiber net is subjected to a hydrophobic surface treatment and then sprayed with nano-silicon dioxide particles and nano-titanium dioxide particles, and the other side is subjected to a hydrophilic surface treatment and then sprayed with nano-zinc oxide particles to obtain a modified collagen fiber net. The collagen polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber; the particle diameter of the nano-silicon dioxide particles is 400nm, the particle diameter of the nano-titanium dioxide particles is 100nm, and the particle diameter of the nano-zinc oxide particles is 250nm; the fineness of the collagen polyester composite fiber is 15D, and the mass ratio of the nano-silicon dioxide particles, the nano-titanium dioxide particles, the nano-zinc oxide particles and the collagen fiber net is 1:1.5:1.2:150.
[0061] S2: preparing a lyocell fiber web from lyocell fiber, soaking the lyocell fiber web in an alkaline solution for 1 hour, taking out and drying the lyocell fiber web to obtain a modified lyocell fiber web; the alkaline solution is a 10% concentration sodium hydroxide solution.
[0062] S3: The modified collagen fiber net in S1 and the modified lyocell fiber net in S2 are stacked in such a way that a modified collagen fiber net is stacked on each side of the modified lyocell fiber net, and a side of the modified collagen fiber net containing nano zinc oxide particles is closely attached to the modified lyocell fiber net to obtain a multi-layer fiber net; the ratio of the total mass of the modified collagen fiber net to the mass of the modified lyocell fiber net is 1:2.
[0063] S4: The multi-layer fiber web in S3 is subjected to the steps of stretching, hydroentanglement and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automotive interior decoration.
[0064] Embodiment 3
[0065] This embodiment prepares a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior nonwoven fabric, and the preparation process is as follows:
[0066] S1: Dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wherein the solvent of the collagen polyester composite solution is a mixture of 4% acetic acid and DMF in a ratio of 2:1, the mass ratio of the collagen fibers to the polyester fibers is 4:6, type I collagen fibers are selected as collagen fibers, and the collagen fibers are hydrolyzed with pepsin before being dissolved, and the mass ratio of pepsin to the collagen fibers is 1:50-200; wet spinning the collagen polyester composite solution, and freeze drying the solution, the freeze drying temperature is -70°C, and the freeze drying time is 40h, to obtain collagen polyester composite fibers.
[0067] The collagen polyester composite fiber is made into a collagen fiber net, and one side of the collagen fiber net is subjected to a hydrophobic surface treatment and then sprayed with nano-silicon dioxide particles and nano-titanium dioxide particles, and the other side is subjected to a hydrophilic surface treatment and then sprayed with nano-zinc oxide particles to obtain a modified collagen fiber net. The collagen polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber; the particle diameter of the nano-silicon dioxide particles is 400nm, the particle diameter of the nano-titanium dioxide particles is 100nm, and the particle diameter of the nano-zinc oxide particles is 250nm; the fineness of the collagen polyester composite fiber is 15D, and the mass ratio of the nano-silicon dioxide particles, the nano-titanium dioxide particles, the nano-zinc oxide particles and the collagen fiber net is 1:1.5:1.2:150.
[0068] S2: preparing a lyocell fiber web from lyocell fiber, soaking the lyocell fiber web in an alkaline solution for 1 hour, taking out and drying the lyocell fiber web to obtain a modified lyocell fiber web; the alkaline solution is a 10% concentration sodium hydroxide solution.
[0069] S3: The modified collagen fiber net in S1 and the modified lyocell fiber net in S2 are stacked in such a way that a modified collagen fiber net is stacked on each side of the modified lyocell fiber net, and a side of the modified collagen fiber net containing nano zinc oxide particles is closely attached to the modified lyocell fiber net to obtain a multi-layer fiber net; the ratio of the total mass of the modified collagen fiber net to the mass of the modified lyocell fiber net is 1:2.
[0070] S4: The multi-layer fiber web in S3 is subjected to the steps of stretching, hydroentanglement and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automotive interior decoration.
[0071] Embodiment 4
[0072] This embodiment prepares a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior nonwoven fabric, and the preparation process is as follows:
[0073] S1: Dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wherein the solvent of the collagen polyester composite solution is a mixture of 4% acetic acid and DMF in a ratio of 2:1, the mass ratio of the collagen fibers to the polyester fibers is 5:5, type I collagen fibers are selected as collagen fibers, and the collagen fibers are hydrolyzed with pepsin before being dissolved, and the mass ratio of pepsin to the collagen fibers is 1:50-200; wet spinning the collagen polyester composite solution, and freeze drying the solution, the freeze drying temperature is -70°C, and the freeze drying time is 40h, to obtain collagen polyester composite fibers.
[0074] The collagen polyester composite fiber is made into a collagen fiber net, and one side of the collagen fiber net is subjected to a hydrophobic surface treatment and then sprayed with nano-silicon dioxide particles and nano-titanium dioxide particles, and the other side is subjected to a hydrophilic surface treatment and then sprayed with nano-zinc oxide particles to obtain a modified collagen fiber net. The collagen polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber; the particle diameter of the nano-silicon dioxide particles is 400nm, the particle diameter of the nano-titanium dioxide particles is 100nm, and the particle diameter of the nano-zinc oxide particles is 250nm; the fineness of the collagen polyester composite fiber is 15D, and the mass ratio of the nano-silicon dioxide particles, the nano-titanium dioxide particles, the nano-zinc oxide particles and the collagen fiber net is 1:1.5:1.2:150.
[0075] S2: preparing a lyocell fiber web from lyocell fiber, soaking the lyocell fiber web in an alkaline solution for 1 hour, taking out and drying the lyocell fiber web to obtain a modified lyocell fiber web; the alkaline solution is a 10% concentration sodium hydroxide solution.
[0076] S3: The modified collagen fiber net in S1 and the modified lyocell fiber net in S2 are stacked in such a way that a modified collagen fiber net is stacked on each side of the modified lyocell fiber net, and a side of the modified collagen fiber net containing nano zinc oxide particles is closely attached to the modified lyocell fiber net to obtain a multi-layer fiber net; the ratio of the total mass of the modified collagen fiber net to the mass of the modified lyocell fiber net is 1:2.
[0077] S4: The multi-layer fiber web in S3 is subjected to the steps of stretching, hydroentanglement and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automotive interior decoration.
[0078] Embodiment 5
[0079] This embodiment prepares a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior nonwoven fabric, and the preparation process is as follows:
[0080] S1: Dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wherein the solvent of the collagen polyester composite solution is a mixture of 4% acetic acid and DMF in a ratio of 2:1, the mass ratio of the collagen fibers to the polyester fibers is 6:4, type I collagen fibers are selected as collagen fibers, and the collagen fibers are hydrolyzed with pepsin before being dissolved, and the mass ratio of pepsin to the collagen fibers is 1:50-200; wet spinning the collagen polyester composite solution, and freeze drying the solution, the freeze drying temperature is -70°C, and the freeze drying time is 40h, to obtain collagen polyester composite fibers.
[0081] The collagen polyester composite fiber is made into a collagen fiber net, and one side of the collagen fiber net is subjected to a hydrophobic surface treatment and then sprayed with nano-silicon dioxide particles and nano-titanium dioxide particles, and the other side is subjected to a hydrophilic surface treatment and then sprayed with nano-zinc oxide particles to obtain a modified collagen fiber net. The collagen polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber; the particle diameter of the nano-silicon dioxide particles is 400nm, the particle diameter of the nano-titanium dioxide particles is 100nm, and the particle diameter of the nano-zinc oxide particles is 250nm; the fineness of the collagen polyester composite fiber is 15D, and the mass ratio of the nano-silicon dioxide particles, the nano-titanium dioxide particles, the nano-zinc oxide particles and the collagen fiber net is 1:1.5:1.2:150.
[0082] S2: preparing a lyocell fiber web from lyocell fiber, soaking the lyocell fiber web in an alkaline solution for 1 hour, taking out and drying the lyocell fiber web to obtain a modified lyocell fiber web; the alkaline solution is a 10% concentration sodium hydroxide solution.
[0083] S3: The modified collagen fiber net in S1 and the modified lyocell fiber net in S2 are stacked in such a way that a modified collagen fiber net is stacked on each side of the modified lyocell fiber net, and a side of the modified collagen fiber net containing nano zinc oxide particles is closely attached to the modified lyocell fiber net to obtain a multi-layer fiber net; the ratio of the total mass of the modified collagen fiber net to the mass of the modified lyocell fiber net is 1:2.
[0084] S4: The multi-layer fiber web in S3 is subjected to the steps of stretching, hydroentanglement and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automotive interior decoration.
[0085] Embodiment 6
[0086] This embodiment prepares a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior nonwoven fabric, and the preparation process is as follows:
[0087] S1: Dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wherein the solvent of the collagen polyester composite solution is a mixture of 4% acetic acid and DMF in a ratio of 2:1, the mass ratio of the collagen fibers to the polyester fibers is 4:6, type I collagen fibers are selected as collagen fibers, and the collagen fibers are hydrolyzed with pepsin before being dissolved, and the mass ratio of pepsin to the collagen fibers is 1:50-200; wet spinning the collagen polyester composite solution, and freeze drying the solution, the freeze drying temperature is -70°C, and the freeze drying time is 40h, to obtain collagen polyester composite fibers.
[0088] The collagen polyester composite fiber is made into a collagen fiber net, and one side of the collagen fiber net is subjected to a hydrophobic surface treatment and then sprayed with nano-silicon dioxide particles and nano-titanium dioxide particles, and the other side is subjected to a hydrophilic surface treatment and then sprayed with nano-zinc oxide particles to obtain a modified collagen fiber net. The collagen polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber; the particle diameter of the nano-silicon dioxide particles is 400nm, the particle diameter of the nano-titanium dioxide particles is 100nm, and the particle diameter of the nano-zinc oxide particles is 250nm; the fineness of the collagen polyester composite fiber is 15D, and the mass ratio of the nano-silicon dioxide particles, the nano-titanium dioxide particles, the nano-zinc oxide particles and the collagen fiber net is 1:1.5:1.2:150.
[0089] S2: preparing a lyocell fiber web from lyocell fiber, soaking the lyocell fiber web in an alkaline solution for 1 hour, taking out and drying the lyocell fiber web to obtain a modified lyocell fiber web; the alkaline solution is a 10% concentration sodium hydroxide solution.
[0090] S3: The modified collagen fiber net in S1 and the modified lyocell fiber net in S2 are stacked in such a way that a modified collagen fiber net is stacked on each side of the modified lyocell fiber net, and a side of the modified collagen fiber net containing nano zinc oxide particles is closely attached to the modified lyocell fiber net to obtain a multi-layer fiber net; the ratio of the total mass of the modified collagen fiber net to the mass of the modified lyocell fiber net is 1:1.7.
[0091] S4: The multi-layer fiber web in S3 is subjected to the steps of stretching, hydroentanglement and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automotive interior decoration.
[0092] Embodiment 7
[0093] This embodiment prepares a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior nonwoven fabric, and the preparation process is as follows:
[0094] S1: Dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wherein the solvent of the collagen polyester composite solution is a mixture of 4% acetic acid and DMF in a ratio of 2:1, the mass ratio of the collagen fibers to the polyester fibers is 4:6, type I collagen fibers are selected as collagen fibers, and the collagen fibers are hydrolyzed with pepsin before being dissolved, and the mass ratio of pepsin to the collagen fibers is 1:50-200; wet spinning the collagen polyester composite solution, and freeze drying the solution, the freeze drying temperature is -70°C, and the freeze drying time is 40h, to obtain collagen polyester composite fibers.
[0095] The collagen polyester composite fiber is made into a collagen fiber net, and one side of the collagen fiber net is subjected to a hydrophobic surface treatment and then sprayed with nano-silicon dioxide particles and nano-titanium dioxide particles, and the other side is subjected to a hydrophilic surface treatment and then sprayed with nano-zinc oxide particles to obtain a modified collagen fiber net. The collagen polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber; the particle diameter of the nano-silicon dioxide particles is 400nm, the particle diameter of the nano-titanium dioxide particles is 100nm, and the particle diameter of the nano-zinc oxide particles is 250nm; the fineness of the collagen polyester composite fiber is 15D, and the mass ratio of the nano-silicon dioxide particles, the nano-titanium dioxide particles, the nano-zinc oxide particles and the collagen fiber net is 1:1.5:1.2:150.
[0096] S2: preparing a lyocell fiber web from lyocell fiber, soaking the lyocell fiber web in an alkaline solution for 1 hour, taking out and drying the lyocell fiber web to obtain a modified lyocell fiber web; the alkaline solution is a 10% concentration sodium hydroxide solution.
[0097] S3: The modified collagen fiber net in S1 and the modified lyocell fiber net in S2 are stacked in such a way that a modified collagen fiber net is stacked on each side of the modified lyocell fiber net, and a side of the modified collagen fiber net containing nano zinc oxide particles is closely attached to the modified lyocell fiber net to obtain a multi-layer fiber net; the ratio of the total mass of the modified collagen fiber net to the mass of the modified lyocell fiber net is 1:2.3.
[0098] S4: The multi-layer fiber web in S3 is subjected to the steps of stretching, hydroentanglement and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automotive interior decoration.
[0099] Embodiment 8
[0100] This embodiment prepares a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior nonwoven fabric, and the preparation process is as follows:
[0101] S1: Dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wherein the solvent of the collagen polyester composite solution is a mixture of 4% acetic acid and DMF in a ratio of 2:1, the mass ratio of the collagen fibers to the polyester fibers is 4:6, type I collagen fibers are selected as collagen fibers, and the collagen fibers are hydrolyzed with pepsin before being dissolved, and the mass ratio of pepsin to the collagen fibers is 1:50-200; wet spinning the collagen polyester composite solution, and freeze drying the solution, the freeze drying temperature is -70°C, and the freeze drying time is 40h, to obtain collagen polyester composite fibers.
[0102] The collagen polyester composite fiber is made into a collagen fiber net, and one side of the collagen fiber net is subjected to a hydrophobic surface treatment and then sprayed with nano-silicon dioxide particles and nano-titanium dioxide particles, and the other side is subjected to a hydrophilic surface treatment and then sprayed with nano-zinc oxide particles to obtain a modified collagen fiber net. The collagen polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber; the particle diameter of the nano-silicon dioxide particles is 400nm, the particle diameter of the nano-titanium dioxide particles is 100nm, and the particle diameter of the nano-zinc oxide particles is 250nm; the fineness of the collagen polyester composite fiber is 15D, and the mass ratio of the nano-silicon dioxide particles, the nano-titanium dioxide particles, the nano-zinc oxide particles and the collagen fiber net is 1:1.5:1.2:150.
[0103] S2: preparing a lyocell fiber web from lyocell fiber, soaking the lyocell fiber web in an alkaline solution for 1 hour, taking out and drying the lyocell fiber web to obtain a modified lyocell fiber web; the alkaline solution is a 10% concentration sodium hydroxide solution.
[0104] S3: The modified collagen fiber net in S1 and the modified lyocell fiber net in S2 are stacked in such a way that a modified collagen fiber net is stacked on each side of the modified lyocell fiber net, and a side of the modified collagen fiber net containing nano zinc oxide particles is closely attached to the modified lyocell fiber net to obtain a multi-layer fiber net; the ratio of the total mass of the modified collagen fiber net to the mass of the modified lyocell fiber net is 1:2.6.
[0105] S4: The multi-layer fiber web in S3 is subjected to the steps of stretching, hydroentanglement and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automotive interior decoration.
[0106] Embodiment 9
[0107] This embodiment prepares a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior nonwoven fabric, and the preparation process is as follows:
[0108] S1: Dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wherein the solvent of the collagen polyester composite solution is a mixture of 4% acetic acid and DMF in a ratio of 2:1, the mass ratio of the collagen fibers to the polyester fibers is 4:6, type I collagen fibers are selected as collagen fibers, and the collagen fibers are hydrolyzed with pepsin before being dissolved, and the mass ratio of pepsin to the collagen fibers is 1:50-200; wet spinning the collagen polyester composite solution, and freeze drying the solution, the freeze drying temperature is -70°C, and the freeze drying time is 40h, to obtain collagen polyester composite fibers.
[0109] The collagen polyester composite fiber is made into a collagen fiber net, and one side of the collagen fiber net is subjected to a hydrophobic surface treatment and then sprayed with nano-silicon dioxide particles and nano-titanium dioxide particles, and the other side is subjected to a hydrophilic surface treatment and then sprayed with nano-zinc oxide particles to obtain a modified collagen fiber net. The collagen polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber; the particle diameter of the nano-silicon dioxide particles is 400nm, the particle diameter of the nano-titanium dioxide particles is 100nm, and the particle diameter of the nano-zinc oxide particles is 250nm; the fineness of the collagen polyester composite fiber is 15D, and the mass ratio of the nano-silicon dioxide particles, the nano-titanium dioxide particles, the nano-zinc oxide particles and the collagen fiber net is 1:1.5:1.2:150.
[0110] S2: preparing a lyocell fiber web from lyocell fiber, soaking the lyocell fiber web in an alkaline solution for 1 hour, taking out and drying the lyocell fiber web to obtain a modified lyocell fiber web; the alkaline solution is a 10% concentration sodium hydroxide solution.
[0111] S3: The modified collagen fiber net in S1 and the modified lyocell fiber net in S2 are stacked in such a way that a modified collagen fiber net is stacked on each side of the modified lyocell fiber net, and a side of the modified collagen fiber net containing nano zinc oxide particles is closely attached to the modified lyocell fiber net to obtain a multi-layer fiber net; the ratio of the total mass of the modified collagen fiber net to the mass of the modified lyocell fiber net is 1:2.9.
[0112] S4: The multi-layer fiber web in S3 is subjected to the steps of stretching, hydroentanglement and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automotive interior decoration.
[0113] Comparative Example 1
[0114] This embodiment prepares a highly efficient moisture-absorbing, breathable and self-cleaning automotive interior nonwoven fabric, and the preparation process is as follows:
[0115] S1: Lyocell fiber is made into a lyocell fiber web, the lyocell fiber web is immersed in an alkaline solution for 1 hour, taken out and dried to obtain a modified lyocell fiber web, the alkaline solution is a 10% concentration of sodium hydroxide solution, the lyocell fiber web is subjected to a hydrophobic surface treatment and then sprayed with nano-silicon dioxide, the particle diameter of the nano-silicon dioxide particles is 400nm, and the mass ratio between the nano-silicon dioxide particles and the lyocell fiber web is: 1:150.
[0116] S3: The modified lyocell fiber web in S1 is subjected to the steps of stretching, hydroentanglement and drying to obtain a moisture-absorbent, breathable and self-cleaning nonwoven fabric.
[0117] Samples of equal weight were taken from Examples 1 to 9 and Comparative Example 1. Except for the temperature being 40° C., the other conditions were tested for hygroscopicity according to the reference standard GB / T21655.1-2008, the air permeability according to GB / T5453-1997, and the contact angle test of the non-woven surface was performed using a contact angle tester. The test results are shown in Table 1 below:
[0118] Table 1 Experimental data of hygroscopicity, air permeability and surface contact angle in Examples 1 to 9 and Comparative Example 1
[0119] Sample source Moisture absorption rate (%) <![CDATA[Air permeability (L*m -2 *S -1 )]]> Contact angle (°) Embodiment 1 478 1672 129.4 Embodiment 2 494 1689 143.7 Embodiment 3 507 1751 147.8 Embodiment 4 500 1735 144.5 Embodiment 5 494 1714 138.6 Embodiment 6 489 1707 141.6 Embodiment 7 522 1782 158.7 Embodiment 8 513 1724 150.9 Embodiment 9 491 1687 143.5 Comparative Example 1 207 1280 98.6
[0120] As can be seen from Table 1, the hygroscopicity, air permeability and contact angle of Examples 1 to 9 are all greater than those of Comparative Example 1, which shows that the preparation method in the present application is superior.
[0121] In Examples 1 to 5, as the mass ratio between collagen fibers and polyester fibers gradually increases, the hygroscopicity, air permeability and contact angle of the nonwoven fabric first increase and then decrease, because the collagen fibers can absorb more water. At the same time, the increase in collagen fibers also helps to improve the air permeability of the nonwoven fabric, because collagen fibers usually have a high porosity, and a proper amount of collagen fibers can form a good network structure with polyester fibers, which improves the self-cleaning property of the nonwoven fabric. However, too much collagen fibers will make the nonwoven fabric susceptible to temperature, reducing hygroscopicity, air permeability and contact angle. The preferred embodiment is Example 3.
[0122] In Example 3 and Examples 6 to 9, as the mass ratio of the total mass of the modified collagen fiber web to the mass ratio of the modified lyocell fiber web gradually decreases, the hygroscopicity, air permeability and contact angle of the non-woven fabric first increase and then decrease. This is because as the mass ratio of the total mass of the modified collagen fiber web to the modified lyocell fiber web gradually decreases, the proportion of lyocell increases, forming a more uniform network structure, improving hygroscopicity, air permeability and contact angle. However, when the proportion is too high, the hydrophilic nature of the lyocell fiber may begin to dominate, causing the structure to be damaged and the hygroscopicity, air permeability and contact angle to be reduced. The preferred embodiment is Example 7.
[0123] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning nonwoven fabric for automobile interior decoration, characterized in that: The following steps are involved: S1: preparing a collagen-polyester composite fiber into a collagen fiber net, performing a hydrophobic surface treatment on one side of the collagen fiber net and then spraying nano-silicon dioxide particles and nano-titanium dioxide particles thereon, and performing a hydrophilic surface treatment on the other side and then spraying nano-zinc oxide particles thereon, to obtain a modified collagen fiber net, wherein the collagen-polyester composite fiber is a composite fiber obtained by mixed spinning of collagen fiber and polyester fiber; S2: preparing a lyocell fiber web from lyocell fibers, soaking the lyocell fiber web in an alkaline solution for 1-2 hours, taking out and drying the lyocell fiber web to obtain a modified lyocell fiber web; S3: stacking the modified collagen fiber web in S1 and the modified lyocell fiber web in S2, wherein one modified collagen fiber web is stacked on each side of the modified lyocell fiber web, and the side of the modified collagen fiber web containing the nano zinc oxide particles is in close contact with the modified lyocell fiber web, to obtain a multilayer fiber web; S4: The multilayer fiber web in S3 is subjected to the steps of stretching, hydroentanglement and drying to obtain a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automobile interior decoration.
2. The method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning nonwoven fabric for automobile interior decoration according to claim 1, characterized in that: The preparation method of the collagen polyester composite fiber in S1 is: dissolving collagen fibers and polyester fibers to obtain a collagen polyester composite solution, wet spinning the collagen polyester composite solution to obtain collagen polyester composite fibers, and the solvent of the collagen polyester composite solution is a mixed solution obtained by mixing acetic acid with a concentration of 2%-5% and DMF in a ratio of 1:1-2:
1.
3. The method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning nonwoven fabric for automobile interior decoration according to claim 2, characterized in that: The mass ratio of the collagen fiber to the polyester fiber is 3:7-5:
5. The collagen fiber is type I collagen fiber. The collagen fiber is hydrolyzed with pepsin before being dissolved. The mass ratio of the pepsin to the collagen fiber is 1:50-200.
4. The method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning nonwoven fabric for automobile interior decoration according to claim 2, characterized in that: After the collagen polyester composite solution is wet-spun, the spun yarn is freeze-dried, the freeze-drying temperature is -85 to -60°C, and the freeze-drying time is 36 to 48 hours.
5. The method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning nonwoven fabric for automobile interior decoration according to claim 1, characterized in that: The particle diameter of the nano silicon dioxide particles in S1 is 400-500 nm, the particle diameter of the nano titanium dioxide particles is 100-200 nm, and the particle diameter of the nano zinc oxide particles is 200-300 nm.
6. The method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning nonwoven fabric for automobile interior decoration according to claim 1, characterized in that: The fineness of the collagen polyester composite fiber in S1 is 10-15D, and the mass ratio of the nano-silicon dioxide particles, the nano-titanium dioxide particles, the nano-zinc oxide particles and the collagen fiber network is: 1:1-1.5:0.8-1.2:100-150.
7. The method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning nonwoven fabric for automobile interior decoration according to claim 1, characterized in that: The alkaline solution in S2 is a sodium hydroxide solution, and the concentration of the alkaline solution is 10-15%.
8. The method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning nonwoven fabric for automobile interior decoration according to claim 1, characterized in that: The mass ratio of the total mass of the modified collagen fiber web in S3 to the mass of the modified lyocell fiber web is 1:2-2.
6.
9. The method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning nonwoven fabric for automobile interior decoration according to claim 1, characterized in that: The spunlace process in S4 is selected from flat mesh spunlace and rotary drum spunlace, and the water pressure of the spunlace process is 60-250 bar.
10. A highly efficient moisture-absorbing, breathable and self-cleaning nonwoven fabric for automotive interior decoration, characterized in that: The invention is prepared according to the method for preparing a highly efficient moisture-absorbing, breathable and self-cleaning non-woven fabric for automobile interior decoration according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method for functional polyester fiber and use method thereof
CN109056100A
Self-cleaning polyester fiber for bedding filling and preparation method of self-cleaning polyester fiber
CN111139550A
Preparation method of collagen spinning stock solution, collagen spinning stock solution and application
CN117089938A
Composite non-woven fabric with biological activity
CN202415905U
Collagen processed fiber, and method for producing the same
JP2024054472A